Asuhan Keperawatan pada Ny. S dengan Bronkopneumonia di Ruang Palm RSUD Dr. Soeselo Kabupaten Tegal - Mukhamad Rizal Hasanudin; Esti Nur Janah; Wawan Hediyanto; Muhammad Silahudin (Stikes Kesdam IV/Diponegoro Semarang, Indonesia, 2024)
Throughout the world, respiratory infections are one of the most serious health problems. Bronchoeumonia is a common respiratory disease that attacks people, especially adults and children. The disease known as acute respiratory infection (ARI) attacks the respiratory tract from the nose to the alveoli in one or several places. ISPA disease manifests as fever, runny nose and cough. ARI can be very dangerous; If left untreated, the disease will spread throughout the respiratory system. People who suffer from this disease will experience breathing problems (Simanjuntak et al., 2021).